Exploratory Factors Structural of The Habitus Mobility - Arger Verstapp Bund (International Journal of Community Service & Engagement, 2022)
The objective of the present work was to establish an exploratory factorial structure of the peri-urban mobility habitus. A non-experimental study was carried out with a non-probabilistic selection of 345 users of the metro public transportation system of Mexico City. The results show that the motivation of the trip is the determinant of the image of the destination, agreeing with the most recent findings, but complementary to the studies carried out around the habitus of peri-urban mobility.